ChemInform Abstract: A Weinreb Amide Approach to the Synthesis of Trifluoromethylketones. Issue 2 (9th January 2013) - Rudzinski, DiAndra M.; Kelly, Christopher B.; Leadbeater, Nicholas E.
Abstract The first case of the Ruppert‐Prakash reagent (II) reacting in a constructive manner with an amide functionality to afford title compounds (III), without formation of over‐trifluoromethylated products is described.